Improving Community Knowledge and Behavior in the One House One Jumantik Program in Dengue Control (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Indonesia is a dengue-endemic country with cases of death every year, including East Kalimantan. One house one jumantik/larva monitor (G1R1J), has been carried out in Samarinda, East Kalimantan but has never been evaluated and implemented. This study aims to determine the communities’ knowledge, attitudes, and actions regarding G1R1J, as well as to see the effect of mentoring by cadres. This research is a quasi-experimental research with a control design. The research activities took time from March - November 2019. Measurements were taken before and after treatment by conducting a pre-test and post-test in Sidodadi Village as an intervention and Dadimulia as a control. The sample size in this study was 300 respondents with the criteria of the occupants of the house/building appointed/person in charge of implementing G1R1J. The instrument used is a questionnaire. T-test statistics are used to determine differences in the control and treatment areas, as well as before and after the intervention. The results showed an increase in knowledge, attitudes, and actions regarding the understanding, symptoms, and causes of dengue fever, as well as about one house one jumantik/larva monitor (G1R1J) after assisting cadres when compared to the control area. There was a statistical difference between the treated areas when compared to the good control areas. Optimum utilization of cadres should be an alternative to reduce the incidence of DHF in the community.